Analysing intersectionality a toolbox of methods - Yang, Keming (Thousand Oaks SAGE Publications, 2024)
his book equips students with the methodological tools to uncover new insights and understand intersectionality in specific social settings. It provides critical examination of long-standing methodologies in intersectionality research
Keywords: Intersectionality (Sociology) -- Research